Effect of horizontal osteotomy level on complication rates and neurosensory deficits after sagittal split ramus osteotomy - Süzen, Muazzez; Uçkan, Sina; Münevveroğlu, Sümer; Özel, Abdullah (Lippincott Williams & Wilkins, 2021)
Horizontal osteotomy is one of the most critical step at sagittal split ramus osteotomy (SSRO) and determination of the ideal height of this horizontal osteotomy is essential to avoid nerve and vessel injury. Purpose: The aim of this study was to evaluate the level of the medial horizontal ramus cut as a risk factor for unfavorable outcomes in the SSRO. Materials and Methods: Sixty-four patients with dentofacial deformity who applied to Oral & Maxillofacial Surgery Department between August 2018 and August 2019 and undergone orthognathic surgery were evaluated. Out of 64, 49 patients had SSRO with or without maxillary surgery and genioplasty. Twenty-six patient had postoperative computed tomography scan with 6-months follow-up. Finally, 26 patient with 52 SSRO sides were included in this study. Computed tomography scans were evaluated and classification according to osteotomy levels was made. Postoperative neurosensory deficit, bleeding, and intraoperative complications such as bad split, visible damage to inferior alveolar bundle were assessed. Age, gender, neurosensory deficit, bad splits were analyzed and correlated with the level of the osteotomies. Results: Fifteen osteotomies were above lingula, 24 between apex and base of lingula, and 14 below lingula. One bad split occurred, and no visible damage to the inferior alveolar bundle was seen. There was no significant difference between osteotomy groups in terms of visual analogue scale (VAS) scores (P > 0.05) but in all groups; women's VAS scores are statistically significantly higher than men. (P: 0.036) Conclusion: There is no correlation between the horizontal osteotomy level and intraoperative or postoperative complications. The low medial horizontal osteotomy can be safely performed in SSRO.
Keywords: Complication; Horizontal Osteotomy; Sagittal Split Ramus Osteotomy